2000
DOI: 10.1103/physrevd.62.063513
|View full text |Cite
|
Sign up to set email alerts
|

Can geodesics in extra dimensions solve the cosmological horizon problem?

Abstract: We demonstrate a non-inflationary solution to the cosmological horizon problem in scenarios in which our observable universe is confined to three spatial dimensions (a three-brane) embedded in a higher dimensional space. A signal traveling along an extra-dimensional null geodesic may leave our three-brane, travel into the extra dimensions, and subsequently return to a different place on our three-brane in a shorter time than the time a signal confined to our three-brane would take. Hence, these geodesics may c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
145
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 116 publications
(148 citation statements)
references
References 15 publications
3
145
0
Order By: Relevance
“…We found [19] that one does not generically obtain the usual Friedmann equation on the observable brane. In fact, by a suitable choice of the bulk energy momentum tensor, one may obtain a Friedmann equation on our brane of the form H 2 ∼ ρ n for any n. More generally, one can obtain other modifications.…”
Section: Braneworld Scenariosmentioning
confidence: 97%
See 2 more Smart Citations
“…We found [19] that one does not generically obtain the usual Friedmann equation on the observable brane. In fact, by a suitable choice of the bulk energy momentum tensor, one may obtain a Friedmann equation on our brane of the form H 2 ∼ ρ n for any n. More generally, one can obtain other modifications.…”
Section: Braneworld Scenariosmentioning
confidence: 97%
“…In fact, by a suitable choice of the bulk energy momentum tensor, one may obtain a Friedmann equation on our brane of the form H 2 ∼ ρ n for any n. More generally, one can obtain other modifications. [20] showed that for an antideSitter bulk one obtains a quadratic correction H 2 ∼ ρ 2 , but more generally one can obtain any power of n, as shown in [19]. The origin of these modifications to the Friedmann equations is as follows.…”
Section: Braneworld Scenariosmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that more creative explanations of large scale smoothness may not involve comparing these two patches. For example, in the context of the brane scenarios, one might imagine that two regions of our observable universe which seem to be causally disconnected might in fact have talked to each other because of a geodesic between them that went off our brane, into the bulk, and then back onto our brane at some distant point, as demonstrated by Chung and Freese [18]. In the remainder of our discussion here we restrict ourselves to the case where eq.…”
Section: Causality Conditionmentioning
confidence: 99%
“…It was noted that the effective speed of light on the brane was variable, depended on the radial position of the brane and could become much smaller than the bulk speed of light (gravitational waves), 1 [17]. It was suggested that such a setup could be used as an alternative to inflation, by utilising the fact that the bulk speed of light was larger than the speed of light on the brane, [17,19].…”
Section: Jhep01(2013)030mentioning
confidence: 99%